Odpowiedź:
z14
[tex] \frac{ { - a}^{11} \times {( - x)}^{9} }{ { - a}^{11} \times {( - x)}^{9} } = 1[/tex]
z16
a)
[tex] \frac{1}{ {x}^{9} } \times {x}^{12} = {x}^{3} \\ x = 0.1 \\ {x}^{3} = 0.001[/tex]
b)
[tex] \frac{9 {x}^{14} + 7 {x}^{14} }{4 {x}^{12} + 5 {x}^{12} } = \frac{ {x}^{14}(9 + 7) }{ {x}^{12} (4 + 5)} = {x}^{2} \frac{16}{9} = \frac{16}{9} \times {x}^{2} \\ x = \frac{3}{4} \\ \frac{16}{9} \times { (\frac{3}{4} )}^{2} = \frac{16}{9} \times \frac{9}{16} = 1[/tex]
niestety nie pomoge ci z ostatnim